PRELIMINARY ANALISYS OF ALCOHOLIC FERMENTATION USING FILTER JUICE, MOLASSES AND SYRUP MIXTURE - Lamas Pérez, Yodalys; de Armas Martínez, Ana Celia; Albernas Carvajal, Yailet; González Suárez, Erenio (Centro Azúcar Journal, 2023)
Introduction: Most of the ethyl alcohol produced is from sugar sources, molasses, but this is becoming more and more sought after due to the increase in biotechnological productions, so it is necessary to study other sources of sugar substrates and/or their mixtures. Objective: To carry out a preliminary study in the alcoholic fermentation stage of the use of filter juice mixture, molasses and syrup. Materials and Methods: A simple trellis-type design of experiments was carried out, performing the preparation of culture media, some as a base and the rest are combinations of them. Up to 100% of sugars in total reducing agents (ART) of the substrates are taken into account. The response variable is alcoholic percentage. Results and Discussion: The fermented musts had percentages between 5.22 and 5.50. The highest was reached in experiments four and five, where the substrates molasses and syrup were used, 5.48 and 5.50 % respectively. On the other hand, when using the juice from the filters (experiments one, two and three), the lowest levels of alcoholic concentration in the medium were obtained, values that differ from those reached in other fermentation studies. Conclusions: The use of syrup in fermentation allows a better utilization of cane that should not be destined for sugar production, given its low quality. In the study, the highest alcoholic percentage is reached when this stream is used as substrate.